Evaluating the psychometric properties of the 7C vaccination readiness scale - Vrdelja, Mitja (Zdravstveno varstvo, 2026)
Vaccine hesitancy remains a major global public health challenge. Psychological models, such as the 7C vaccination readiness scale, aim to identify key psychological determinants of vaccine uptake. While the scale has shown validity in various cultural contexts, its psychometric properties have not yet been evaluated in Slovenia. Methods This study assessed the psychometric properties, convergent validity, and criterion validity of the Slovenian version of the 7C scale using a representative sample of 1,350 adults via confirmatory factor analysis (CFA), correlation coefficients, and regression analyses. Results The bifactor model showed mixed psychometric properties. CFA revealed a weak model fit, with two items showing inadmissible estimates; these were removed. The revised model showed improved estimation and acceptable, though still suboptimal, fit indices. Convergent validity was supported by significant correlations between the general vaccination readiness factor and conspiracy beliefs, while individual components showed weaker associations. Criterion validity analyses showed that the general factor was the strongest predictor of vaccination intention, with calculation and compliance also contributing. The 7C model explained more variance in vaccination intention than the 5C model, suggesting greater utility. Despite structural limitations, the scale demonstrates practical value and offers recommendations for refinement. Conclusions The Slovenian version of the 7C scale proved to be a valuable tool for predicting vaccination intention. The general factor was a robust predictor, and calculation and compliance showed additional validity. However, components like complacency and constraints need revision to improve model fit. With refinement, the 7C scale holds promise for research and public health applications across contexts.
Keywords: 7C vaccination readiness scale; Cepljenje (medicina); lestvica 7C pripravljenost na cepljenje; oklevanje glede cepljenja; psihometrične lastnosti; psychometric properties; vaccine hesitancy